Beyond 'rights-based approaches'? Employing a process and outcomes framework. Issue 5 (28th May 2019) - Miller, Hannah; Redhead, Robin
ABSTRACT: The protection and promotion of human rights is experiencing increased commitment around the globe. Many organisations, groups and movements have strategically employed 'rights-based' agendas in order to advance issues and accomplish particular objectives. However, despite this ongoing mainstreaming and dominance, there is little time to reflect on the efficacy, sustainability and shortcomings of taking rights-based approaches. In this introduction to the volume 'Beyond 'rights-based approaches'?' we think critically about – and beyond – 'rights-based' approaches. As part of our review of the existing literatures (which we organise around three key waves in rights-based focused research), we introduce new research that seeks transformative solutions to systemic patterns of injustice, while considering the real changes in peoples' lives. Central to our discussion is the proposal and then the deployment of a new framework, based on a 'process/outcome axis'. From this vantage point we identify and discuss how our contributors challenge the prevailing assumptions and practices in the fight for human dignity, by addressing the gap between theory and practice, and between scholars, activists and practitioners.